The Effect of Emotional Freedom Techniques Therapy towards Learning Concentration Level of Students - Ni Komang Matalia Gandari; I Gusti Ngurah Arya Sentana (Universitas Triatma Mulya, 2018)
Background. Concentration can determine individual learning achievement. Concentration can be enhanced by implementing Emotional Freedom Techniques (EFT) therapy method, because EFT can increase the learning concentration by stimulating the limbic system. The study aimed at identifying the effect of Emotional Freedom Techniques (EFT) Therapy on Student Learning Concentration. Methods. The research method used in this study was quasi experimental design with the untreated control group design with dependent pre-test and post-test samples. The number of samples in the study was 30 respondents, divided into intervention and control groups using non-probability sampling technique of purposive sampling. The intervention group was given EFT within 30 minutes, three times, and for two weeks. Before and after intervention, the level of learning concentration was measured by using a psychological scale. Data analysis used in this study was t-test. Results. The results showed that there was a significant differences between learning concentration level before and after being implemented EFT intervention (p<0.05) and there was a significant difference in the concentration of learning after being given the intervention between the experimental and control groups (p<0.05). Conclusion. It could be concluded that EFT can improve the concentration of individual learning especially adolescents. The use of EFT is supported by empirical evidence, using simple techniques, easy to be conducted by anyone, and gives no side effects.